PSIKOEDUKASI MELALUI PERMAINAN GERAK DAN LAGU UNTUK MELATIH KONSENTRASI PADA ANAK SD NEGERI DESA RAJA - Mawaddah Rizki; Mutia Mawardah (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Psychoeducation is an activity carried out to increase understanding and/or skills as an effort to prevent the emergence or spread of psychological disorders in a group, community or society or activities carried out to increase understanding for the environment, especially the family, about disorders experienced by a person. Movement and songs for elementary school children are learning models to stimulate children's musical and kinesthetic intelligence. The purpose of this field work practice (PKL) is (1) to provide appropriate psychoeducation and/or stimulation to develop children's learning abilities (2) to understand the relationship between movement and songs on children's learning abilities (3) to build the mood of students so they can feel comfortable in learning and following the learning process given by the teacher. The method used in this fieldwork practice is the planning method. The target in this program is elementary school students. Data collection techniques using observation, interview, and documentation. The results of the field work practice: (1) The creation of various kinds of crafts such as flowers and paintings at Raja Village Elementary School (2) The creation of children's motivation to be more enthusiastic about starting learning (3) The creation of teacher awareness of the importance of raising the mood of students.